Multicultural education: the state of play from an Australian perspective. Issue 1 (2nd January 2016) - Watkins, Megan; Lean, Garth; Noble, Greg
Abstract : This article reports on the first comprehensive survey of public school teachers in the Australian state of New South Wales (NSW) around issues of multicultural and English as Second Language (ESL) education. While there is substantial literature on multicultural education – what it should and shouldn't be – there is much that is left unexplored in research in the area, not least of which is the characteristics of the teaching labour force. In this article, we 'take stock' of multicultural education, not by engaging with philosophical debates about multiculturalism as an ethical or policy practice, but as an auditing of what exists in the name of multicultural education. Drawing on a sample of over 5000 respondents, the article documents the changing cultural profile of the profession and highlights gaps in pre-service training and professional learning of teachers in terms of meeting the needs of Australia's increasingly culturally and linguistically complex school populations.